Auto-translacja jaźni - Chromik, Anna (Er(r)go. Teoria - Literatura - Kultura, 2005)
Anna Chromik's review of "Translating One's Self. Language and selfhood in cross-cultural autobiography" by Mary Besemeres (2002).